2021
DOI: 10.3389/fncel.2021.639322
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between ATP-P2X7 and Adenosine A2A Receptors Controlling Neuroinflammation in Rats Subject to Repeated Restraint Stress

Abstract: Depressive conditions precipitated by repeated stress are a major socio-economical burden in Western countries. Previous studies showed that ATP-P2X7 receptors (P2X7R) and adenosine A2A receptors (A2AR) antagonists attenuate behavioral modifications upon exposure to repeated stress. Since it is unknown if these two purinergic modulation systems work independently, we now investigated a putative interplay between P2X7R and A2AR. Adult rats exposed to restraint stress for 14 days displayed an anxious (thigmotaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…The authors discovered increased expression of P2X7R and A 2A receptor in the hippocampus and prefrontal cortex. Next, they showed that BBG a P2X7R-selective antagonist and caffeine an A 2A receptor antagonist attenuated the depressive phenotype ( 325 ).…”
Section: Metabolic Pathways In Microgliamentioning
confidence: 99%
“…The authors discovered increased expression of P2X7R and A 2A receptor in the hippocampus and prefrontal cortex. Next, they showed that BBG a P2X7R-selective antagonist and caffeine an A 2A receptor antagonist attenuated the depressive phenotype ( 325 ).…”
Section: Metabolic Pathways In Microgliamentioning
confidence: 99%
“…In this regard, Ciruela et al (2006) demonstrated in radioligand‐binding experiments in co‐transfected cells and rat striatum that heteromerization of A 1 and A 2A Rs allows adenosine to exert a fine‐tuning modulation of glutamatergic neurotransmission since activation of A 2A Rs reduces the affinity of the A 1 Rs for agonists. Likewise, there are several examples in different preparations of a functional cross‐talk between P2 and P1 Rs (e.g., Dias et al, 2021; Tonazzini et al, 2007, reviewed by Agostinho et al, 2020). Besides, other factors such as the topographical arrangement of ecto‐enzymes, transporters and other presynaptic Rs may also influence the effects mediated by A 1 , A 3 , or A 2A Rs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2A R up-regulation mostly occurs in synapses, in accordance with the involvement of synaptic alterations at the onset of most brain diseases (e.g., Rebola et al, 2005;Kaster et al, 2015;Viana da Silva et al, 2016;Canas et al, 2018), but is also observed in glia cells in the progression of chronic brain diseases (Matos et al, 2012;Orr et al, 2015;Barros-Barbosa et al, 2016;Patodia et al, 2020). It is still unclear if this A 2A R up-regulation only involves an increased readout of A 2A R mRNAs (Canas et al, 2018) or also involves an overexpression of A 2A R mRNA, which has been reported in the dysfunctional or diseased brain (e.g., Costenla et al, 2011;Espinosa et al, 2013;Hu et al, 2016;Dias et al, 2021). In fact, the triggers and mechanisms of this A 2A R up-regulation in the diseased brain are essentially unknown.…”
Section: Up-regulation Of Adenosine a 2a Receptors In Brain Diseasesmentioning
confidence: 99%